Costos de los servicios hospitalarios y su incidencia en el presupuesto del Hospital Básico N°11 “Galápagos”, Riobamba período 2018 - Ana Lucía, Morocho Hipo (2021)
ABSTRACT This research was developed in the Basic Hospital N°11 Galápagos. Its main objective was to analyze the costs of Hospital services and their impact on the 2018 Budget, providing adequate and timely information for decision making and Budgetary bread making. The study was carried out through the problem, objectives, theoretical framework, and the establishment of the methodology, which was deductive, reflecting the general conditions to the specific, descriptive being the analysis of the allocation of cost hospital services. The information was obtained in documentary way interviews and surveys in the areas of the hospital. The development was carried out in two stages. The existing hospital services that the military hospital frequently provided care for were identified—getting a record of 14.348 patients who attended in 2018. The military institution is limited to a budget. It uses computer programs and instruments that reflect the entity's financial management. It is a regulated entity in external medicine, internal medicine, pediatrics, traumatology, dentistry, general surgery, gynecology, and nutrition. It is a public institution. KEYWORDS Hospital Costs, Hospital services, Expenses, Budget. Reviewed by: Mgs. Ana Maldonado León ENGLISH PROFESSOR C.I.0601975980